Cutaneous actinomycosis: the great mimicker - Ngow, Harris Abdullah; Wan Mohd Nowalid, Wan Khairina (BMJ Publishing Group Ltd & Association of Clinical Pathologists, 2009)
Actinomycosis is an indolent, suppurative and chronic granulomatous infection caused by a Gram-positive organism that was initially thought to be a fungus. 12 Actinomycosis is rare with estimated incidence of one case per institution per year, with male predominance.3 Precipitating factors of cervicofacial infection are related to dental and maxillofacial trauma. We describe an interesting case of facial actinomycosis that was misdiagnosed as sebaceous cyst and revealed later by histopathological findings of the tissue biopsy.